FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA ANAK BALITA - Marliany, Heni; Apipudin, Aap; Ramdani, Ary Syahrul (LPPM STIKes Muhammadiyah Ciamis, 2022)
The World Health Organization (WHO) estimates that 54% of child deaths in the world are caused by malnutrition. Nutrition is one of the important factors in determining the quality of human resources in which it has a close relationship with health and intelligence. Based on data information from the Ciamis Health Center there are 53 cases of children under five who have nutritional problems in Benteng Village. Objective: to determine the relationship between parental knowledge, children's diet, infectious diseases and nutritional status in children under five in Benteng Village, Ciamis District, Ciamis Regency. Methods: this study uses quantitative analytical methods with a cross sectional research design. The population in this study were 307 children under five in Benteng Village. Sampling in this study using purposive sampling as many as 33 respondents. Results: the results of the study based on the Chi-Square test, the significance of p between parents' knowledge and nutritional status was 0.573. Chi-Square test, the significance of p between children's diet and nutritional status is 0.147. Chi-Square test, the significance of p between infectious diseases and nutritional status is 0.111. Conclusion: there is no relationship between parental knowledge, children's diet, infectious diseases and nutritional status of children under five in Benteng Village, Ciamis District, Ciamis Regency.